2021
DOI: 10.1021/acs.cgd.1c00140
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Mg-Orthocarbonate through the Reaction MgCO3 + MgO = Mg2CO4 at Earth’s Lower Mantle PT Conditions

Abstract: Orthocarbonates of alkaline earth metals are the newly discovered class of compounds stabilized at high pressures. Mg-orthocarbonates are the potential carbon host phases, transferring oxidized carbon in the Earth’s lower mantle up to the core–mantle boundary. Here, we demonstrate the possibility for the formation of Mg2CO4 in the lower mantle at pressures above 50 GPa by ab initio calculations. Mg2CO4 is formed by the reaction MgCO3 + MgO = Mg2CO4, proceeding only at high temperatures. At 50 GPa, the reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 49 publications
6
30
2
Order By: Relevance
“…Subsequent experimental synthesis has confirmed the existence of this structure at a pressure above 20 GPa or possibly lower . Recently, we have also shown the existence of Mg-orthocarbonate, which is stabilized at pressures above 50 GPa . Our results on the stability of the orthocarbonates of the other alkaline-earth metals, in particular Sr 2 CO 4 - Pnma , have been presented in the form of a conference presentation and the corresponding book of abstracts .…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Subsequent experimental synthesis has confirmed the existence of this structure at a pressure above 20 GPa or possibly lower . Recently, we have also shown the existence of Mg-orthocarbonate, which is stabilized at pressures above 50 GPa . Our results on the stability of the orthocarbonates of the other alkaline-earth metals, in particular Sr 2 CO 4 - Pnma , have been presented in the form of a conference presentation and the corresponding book of abstracts .…”
Section: Introductionsupporting
confidence: 60%
“…However, some of the structures of orthocarbonates are dynamically stable and can be recovered on decompression after high-pressure synthesis. Totally, there are five such structures: Mg 2 CO 4 - Pnma , Mg 2 CO 4 - P 2 1 / c , Ca 3 CO 5 - Cmcm , Sr 2 CO 4 - Pnma , and Sr 3 CO 5 - Cmcm . This is nearly 50% of the known structures of alkaline-earth orthocarbonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the established orthoanions, it was recently predicted and experimentally shown that carbonates with [CO 4 ] 4– groups may even be recovered at ambient conditions. , Further, stable structures with stoichiometries M 2 [CO 4 ] and M 3 [CO 4 ]O (M = Mg, Ca, Sr, and Ba) have been predicted by DFT-based calculations. Here, we report the successful outcome of the synthesis of one of these structures using M = Sr. In contrast to earlier syntheses, we obtained a carbonate with an antiperovskite structure, where the oxygen anion is coordinated by six Sr cations.…”
mentioning
confidence: 72%
“…Tetrahedral coordination implies the presence of C-sp 3 hybrid orbitals. Initially, such sp 3 carbonates were obtained as high-pressure polymorphs of conventional carbonates at very high pressures ( p > 70 GPa) and high temperatures (a few thousand Kelvin) and were thought to exist only at these extreme conditions. This situation changed when, instead of transforming carbonates by pressure, novel sp 3 carbonates were formed by reactions. Guided by density functional theory (DFT)-based predictions, alkaline-earth oxides were reacted with the corresponding carbonates at high temperatures and Sr 2 [CO 4 ]- Pnma and isostructural Ca 2 [CO 4 ]- Pnma were formed in a laser-heated diamond anvil cell (LH-DAC) at ≈20 GPa. …”
mentioning
confidence: 99%